2007
DOI: 10.1093/glycob/cwm044
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical characterization of galectin from amphioxus: primitive galectin of chordates participated in the infection processes

Abstract: A novel F4-carbohydrate recognition domain (CRD)-linker-F3-CRD-type bi-CRD Branchiostoma belcheri tsingtauense galectin (BbtGal)-L together with its alternatively spliced mono-CRD isoform BbtGal-S from amphioxus intestine was encoded by a 9488-bp unique gene with eight exons and seven introns. The recombinant proteins of BbtGal were found to have beta-galactoside-binding activity, indicating that BbtGal was a member of the galectin family. Phylogenetic analysis of this gene along with its splicing form and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Immunocytes (coelomocytes) of amphioxus were first discovered in the gut region 25 yr ago (Rhodes et al 1982). Our studies have further confirmed that gill and gut represent the major immune region in amphioxus Yu et al 2005Yu et al , 2007bHuang et al 2007a,b;Yuan et al 2007). Unfortunately, since the year 1982, only a few studies address the amphioxus immunity.…”
supporting
confidence: 74%
“…Immunocytes (coelomocytes) of amphioxus were first discovered in the gut region 25 yr ago (Rhodes et al 1982). Our studies have further confirmed that gill and gut represent the major immune region in amphioxus Yu et al 2005Yu et al , 2007bHuang et al 2007a,b;Yuan et al 2007). Unfortunately, since the year 1982, only a few studies address the amphioxus immunity.…”
supporting
confidence: 74%
“…All galectins contain either one or two evolutionary conserved CRDs [2], and have been distinguished into three groups: (1) prototype galectins (one CRD); (2) tandem type galectins, composed of two CRDs, homologous but not identical, connected by a short linker peptide (Bi-CRD); and (3) chimeric type galectins (one CRD and one regulatory domain). The vertebrate Bi-CRD galectins are always encoded by three exons with two subtypes: N-terminal F4 subtype CRD and the C-terminal F3 subtype CRD (F4-CRDs and F3-CRDs) [3]. Also the exon/intron organization of the echinoderm Strongylocentrotus purpuratus and the amphioxus Branchiostoma belcheri galectins [3] is very similar to their vertebrate orthologues.…”
Section: Introductionmentioning
confidence: 98%
“…The vertebrate Bi-CRD galectins are always encoded by three exons with two subtypes: N-terminal F4 subtype CRD and the C-terminal F3 subtype CRD (F4-CRDs and F3-CRDs) [3]. Also the exon/intron organization of the echinoderm Strongylocentrotus purpuratus and the amphioxus Branchiostoma belcheri galectins [3] is very similar to their vertebrate orthologues. Galectins are mainly cytosolic, and exert extracellular functions by the binding to and cross-linking of glycan groups of glycoproteins and/or glycolypids on the surface of various cell types [4].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, the expression of SgCTL-1 could be more significantly up-regulated by PGN, which was different with other mollusk C-type lectins [5,54], suggesting the main function of SgCTL-1 might be recognizing gram-positive bacteria and triggering relative immune responses. Although the mRNA expression of other galectins, such as galectins from scallop and amphioxus was significantly up-regulated after challenge of both gram-positive and gram-negative bacteria, they were almost stable during the fungi stimulation [40,55]. In present study, SgGal-1 expression could be significantly up-regulated by all the three PAMPs from gram-negative bacteria, gram-positive bacteria and fungi, exhibiting its wide recognition spectrum.…”
Section: Discussionmentioning
confidence: 42%